Transformation of water use in tianjing areas in residential houses following the installation of piped water systems - Yanhan Wu; Satoshi Boda; Shin-Ya Nishimura; Yingqing Fei; Wenhao Ji (Journal of Asian Architecture and Building Engineering, 2025)
Government-led rural water supply initiatives in China have negatively impacted the diversity of traditional waterheads, with rebuilt riverbanks and filled wells indicating the spatial and functional loss of water use. However, tianjing (courtyard) residential houses have demonstrated so sustainable changes in water use that it is needed to study how villagers have improved water use following the introduction of piped water systems. This research methodology subdivides the relationship between traditional elements, modern equipment, and functional changes based on the correspondence between space and behaviour in traditional architectural planning. To sidestep the weaknesses of historical texts, GIS, and simulation and analysis software to link space and behaviour, this survey method uses measurements, interviews, photographic recordings, and regression analysis. Although residences have different spatial features in tianjing and kitchen areas, they consistently reduce the impact of tap water on oil-related cooking techniques by maintaining an adequate distance between running water and cooking equipment, installing partition walls between the kitchen area and tianjing, and using clay ovens with honeycomb briquettes. This change from plural traditional water sources to a single modern water supply not only maintains the pre-existing elements but also revitalises water use through the integration of modern equipment.